COMBINATION OF DIDACTIC LECTURES WITH PROBLEM-BASED LEARNING SESSIONS IN ANATOMY: A COHORT STUDY. - Keshri, Ravi (Student’s Journal of Health Research Africa, 2024)
Background Anatomy and its functional application in clinical practice require a thorough understanding of the subject. During the initial college years, a didactic method of teaching is followed which limits the understanding of its application further in a clinical setting. Problem-based learning session aids in a better understanding of the anatomy. In this study, a judicious combination of didactic learning and problem-based learning is assessed based on feedback received from the student and their overall performance. Method The students of the first year of medical college were taken for study. The batch of 100 students were taught endocrinology, then they were given a problem-based questionnaire based on their current knowledge. They were divided into small groups for discussion and the method was evaluated based on the feedback received from the students. Results 80% of students found the mixture of didactic lectures and PBL very effective, 13% effective, and 7% ineffective. Similarly, 80% found the approach relevant to their anatomy studies, 13% somewhat relevant, and 7% irrelevant. Academically, the combined method led to a 15% average improvement in exam scores. Additionally, 66% credited PBL for their exam success, 31% saw some benefit, and 3% noted no benefit. Conclusion It is not possible to teach and learn anatomy with a single approach. A mixture of multiple techniques such as didactic teaching as well as problem-based learning helps in a better understanding of the subject and makes it easier for its application in clinical practice. Recommendation Along with didactic lectures, problem-based learning methodology should be implemented in an academic setting to further enhance the outcomes of learning in the clinical setting